2015
DOI: 10.1371/journal.pone.0140808
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Mediate Female-Dominant IL-4 Production and Airway Inflammation in Allergic Asthma

Abstract: The prevalence and severity of bronchial asthma are higher in females than in males after puberty. Although antigen-specific CD8+ T cells play an important role in the development of asthma through their suppressive effect on cytokine production, the contribution of CD8+ T cells to sex differences in asthmatic responses remains unclear. In the present study, we investigated the sex-specific effect of CD8+ T cells in the suppression of asthma using an ovalbumin mouse model of asthma. The number of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(41 reference statements)
0
13
0
1
Order By: Relevance
“…Several clinical studies reported a significant increase in the percentage of CD4+ and CD8+ T cells producing IL-4 in asthmatic children. 22,23 This finding suggests that IL-4 is not only produced by CD4+ Th2 cells, but also by CD8+ T cells. While it is well established that CD4+ T lymphocytes play a crucial role in the initiation, progression, and persistence of asthma, the role of CD8+ T cells is less understood.…”
Section: Discussionmentioning
confidence: 91%
“…Several clinical studies reported a significant increase in the percentage of CD4+ and CD8+ T cells producing IL-4 in asthmatic children. 22,23 This finding suggests that IL-4 is not only produced by CD4+ Th2 cells, but also by CD8+ T cells. While it is well established that CD4+ T lymphocytes play a crucial role in the initiation, progression, and persistence of asthma, the role of CD8+ T cells is less understood.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have reported that the expression of its granular proteins has functions relevant to the features of asthma, including histopathologic changes, reversible airway narrowing, and bronchial hyperreactivity [ 41 44 ]. The activated T cells in the airway wall are associated with inflammation of asthma [ 45 , 46 ], and the subsets of T cell antigens have attracted extensive attention by researchers, such as the T cells of CD4+(T helper) [ 47 51 ], CD8+ [ 52 54 ], CD25+ [ 55 ], CD28 [ 56 , 57 ], CD29 [ 58 , 59 ], CD39+, and CD73 [ 60 63 ]. The imbalance of different subsets and the regulatory mechanism are the research emphasis of this field [ 64 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoalveolar lavage (BAL) fluids were prepared as previously described [25]. Briefly, BAL samples collected on day 5 after OVA inhalation (with 2 × 0.25 mL chilled PBS through a cannula inserted in the trachea) were centrifuged at 450 g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…For cytokine assay, the entire lungs were excised 1 day after OVA inhalation and homogenized in chilled 0.1% Triton-X PBS with 1% protease inhibitor (Sigma-Aldrich). After centrifugation at 15,000 g for 15 min at 4°C, the supernatants were stored at −80°C [25].…”
Section: Methodsmentioning
confidence: 99%